Deposition scenarios from Baltic Sea ship traffic with scrubbers - Claremar, Björn; Rutgersson, Anna (Uppsala University, 2018)
A change in regulation for maximum sulfur content in maritime fuel, in 2015 from 1 to 0.1 %, decreases the atmospheric sulfur concentration and deposition significantly. However, due to costs related to refining, the cleaning of exhausts through scrubbers has become a possible economic solution. Open-loop scrubbers meet the air quality criteria but their consequences for the marine environment are largely unknown. The resulting potential of future acidification in the Baltic Sea, both from atmospheric deposition and from scrubber water along the shipping lanes, based on different assumptions about sulfur content in fuel, scrubber usage, and increased shipping density has been assessed. This database contains shipping and scrubber scenarios for atmospheric deposition and scrubber exhaust from the period 2011 to 2050.

When using this dataset, please also cite: Claremar B., K. Haglund, A. Rutgersson. Ship Emissions and the use of current air cleaning technology: Contributions to air pollution and acidification in the Baltic Sea. Accepted for publication in Earth Syst. Dynam., 8, 1–19, 2017.

Databasen innehåller frakt- och skrubberscenarier för atmosfärisk avsättning och skrubberutblåsning för perioden 2011 till 2050.

När du använder det här datasetet, citeras även: Claremar B., K. Haglund, A. Rutgersson. Ship Emissions and the use of current air cleaning technology: Contributions to air pollution and acidification in the Baltic Sea. Accepted for publication in Earth Syst. Dynam., 8, 1-19, 2017.

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0245
Deposition scenarios from Baltic Sea ship traffic with scrubbers
Keywords: ATMOSPHERIC NITRIC ACID; NITROGEN OXIDES; SULFUR DIOXIDE; SULFATE; TRANSPORTATION; ACID DEPOSITION; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi